Influence of a sodium formate/formic acid mixture on growth of juvenile common carp (Cyprinus carpio) fed different fishmeal replacement levels of detoxified Jatropha curcas kernel meal in practical, mixed diets. Issue 2 (3rd April 2018) - Krome, Carsten; Schuele, Fabian; Jauncey, Kim; Focken, Ulfert
ABSTRACT: Intensification of cyprinid production has resulted in substantial increases in aquafeed demand for these species and a requirement for studies on new protein sources. Increased availability of presscakes from biodiesel crops may help to meet this requirement. The suitability of detoxified Jatropha curcas kernel meal (JKM), in combination with a dietary organic acid/salt blend (NDF), was tested in practical diets for juvenile common carp ( Cyprinus carpio ). Four treatment diets contained between 0% and 13.5% fishmeal with the fishmeal protein replaced by JKM (0%, 30%, 70%, and 100%). Four further diets of the same composition but including 0.5% NDF were also prepared, and all diets were fed to carps for eight weeks. There were no statistical differences in growth between diets containing JKM and the control. Furthermore, addition of dietary NDF significantly improved final weights, specific growth rates, feed conversion ratios, and protein efficiency ratios. Body composition analysis showed a significant impact of dietary JKM inclusion on increasing body lipid content. The addition of NDF showed a tendency to lower body lipid content (P = 0.11). JKM is a suitable protein source in diets for carp, and the inclusion of 0.5% of NDF proved to be beneficial.